Environmental Wisdom in Oral Literature of Arjuna Slopes People - Sukmawan, Sony - (Bina Nusantara University, 2018)
This study sought to describe the orientation, representation, and the relationship of oral literary texts of the Slopes Arjuna towards its nature, poetical characteristics and literary texts narrative by using ecocriticism theory. The interdisciplinary approach used to understand the data were ecocritics, literary, ethical approach to the environment, cultural approach, and folkloristic approach. The instruments used were observation and in-depth- interview. The research was conducted on the slopes of Mount Arjuna, East Java from November 2012 to February 2014. The result shows that the range of oral literature texts of Arjuna Slopes communities explicitly and implicitly, intensively and extensively, show the orientation towards nature. It shows that the oral literature of Arjuna slope people obtains the pastoral narrative and apocalyptic narrative. The study also reveals the presence of biological nature and the psychological nature which are conveyed explicitly and demonstrated in its vitality. The texts orientation towards nature is more detailed presented in the various forms of nature. Nature orientation occurred in the text becomes an emphatic and important marker of environmental wisdom literature. Furthermore, the characteristics of environmental wisdom literature which are identified and constructed based on the review of the public oral literature of Slopes Arjuna have its distinctiveness. This peculiarity is seen in the breath of cosmocentric-spirituality born from harmony syncretization between spirituality Kejawen, Islami Sarengat, Hindu-Buddhist mysticism, as the source of wisdom of environmental values in the society of Slopes Arjuna oral literature.